Tracing Trends in Educational Research on Creative Problem Solving: A Bibliometric Analysis (2007-2024) - Nury Yuniasih; Wahyu Sopandi; Andi Suhandi; Ernawulan Syaodih (AL-ISHLAH: Jurnal Pendidikan, 2025)
Creative Problem Solving (CPS) enhances adaptability, fosters innovation, and improves productivity. However, integrating CPS in education remains challenging. This study examines trends, key themes, and gaps in CPS research within education from 2007 to 2024 through bibliometric analysis. Data was collected from Scopus due to its extensive interdisciplinary coverage and credibility in indexing peer-reviewed journals in education, psychology, and cognitive sciences. A total of 68 publications were selected based on relevance to CPS in education and journal type. The analysis focused on publication trends, thematic developments, and methodological approaches. Findings indicate that traditional curricula emphasizing rote memorization hinder CPS integration. Innovative approaches such as problem-based learning, project-based learning, and STEM education offer potential solutions. Between 2007 and 2018, research mainly explored CPS concepts. In 2019, the focus shifted towards instructional models, with 2020 marking the peak of CPS-related publications. Strategies supporting CPS development include automated assessment tools, flipped learning, and interdisciplinary approaches. Thematic analysis highlights the connection between CPS, creativity, and problem-solving. The study identifies significant advancements in CPS research, with implications for curriculum development, teacher training, and policy-making. Emerging technologies, including artificial intelligence (AI) and virtual reality (VR), show promise in expanding CPS applications in education. Future research should explore technology-enhanced CPS strategies to further enhance problem-solving skills across various educational contexts.